Identification of isolates of the plant pathogen Leptosphaeria maculans with resistance to the triazole fungicide fluquinconazole using a novel in planta assay - Van De Wouw, A.; Elliott, V.; Chang, S.; Lopez-Ruiz, Fran; Marcroft, S.; Idnurm, A. (Public Library of Science, 2017)
Leptosphaeria maculans is the major pathogen of canola (oilseed rape, Brassica napus) worldwide. In Australia, the use of azole fungicides has contributed to the 50-fold increase in canola production in the last 25 years. However, extensive application of fungicides sets the stage for the selection of fungal populations with resistance. A high-throughput in planta assay was developed to allow screening of thousands of isolates from multiple populations. Using this screen, isolates were identified with decreased sensitivity to the fungicide fluquinconazole when applied at field rates as a protective seed dressing: these isolates cause significantly larger lesions on cotyledons and true leaves and increased disease severity at plant maturity. This increased in planta resistance was specific to fluquinconazole, with no cross resistance to flutriafol or tebuconazole/prothioconazole. In a limited set of 22 progeny from a cross between resistant and susceptible parents, resistance segregated in a 1:1 ratio, suggesting a single gene is responsible. A survey of 200 populations from across canola growing regions of Australia revealed fungicide resistance was present in 15% of the populations. Although in vitro analysis of the fungicide resistant isolates showed a significant shift in the average EC 50 compared to the sensitive isolates, this was not as evident as the in planta assays. The development of this novel, high-throughput in planta assay has led to the identification of the first fungicide resistant L. maculans isolates, which may pose a threat to the productivity of the Australian canola industry.